Frequency of Malignancy in Multinodular Goitre (Bangladesh Journal of Otorhinolaryngology, 2015)
Objectives: To determine the frequency of thyroid carcinoma in clinically or sonogragraphically multinodular goitre in patients undergoing thyroidectomy Setting: This is a cross sectional study was carried out at the Department of Otolaryngology and Head-Neck Surgery, Bangabandhu Sheikh Mujib Medical University during the period from January 2012 to June 2012. Methods: This study includes all the patients admitted in Otolaryngology and Head-Neck surgery department of Bangabandhu Sheikh Mujib Medical University having diagnosis of multinodular goitre & underwent thyroidectomy. All patients with non-toxic multinodular goitre (clinically or sonographically) irrespective of age , sex was be included . Results: Out of 50 patients, 41 patients (82%) were female, and 9 patients (18%) were male with a female to male ratio 4.5: 1. This shows female preponderance of multinodular goitre. Out of 50 patients, 5 patients had histologicaly proven thyroid malignancy (4 females and 1 male). In this study overall incidence of carcinoma in multinodular goitre was 10% and female to male ratio 4:1 with the incidence in female was 9.75% and in male 11.11. The incidence of malignancy under 21 years was 50% and above 21 years was 8.33%. Regarding the types of malignancy in this series, papillary carcinoma was the most common variety (80%) followed by follicular carcinoma (20%). DOI: http://dx.doi.org/10.3329/bjo.v20i2.22022 Bangladesh J Otorhinolaryngol; October 2014; 20(2): 75-79